2016
DOI: 10.3390/jcm5100088
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Parental Emotional Neglect on Assault Victims Seeking Treatment for Depressed Mood and Alcohol Misuse: A Pilot Study

Abstract: This study explores the relationship between reported parental emotional neglect when a child, assault type experienced, posttraumatic stress symptoms (PTSS), depression, and alcohol consumption in treatment seekers for comorbid depressive symptoms and alcohol misuse. Participants (n = 220) with concurrent depression and alcohol misuse were recruited from the DAISI (Depression and Alcohol Integrated and Single-focussed Interventions) project. Assault type and PTSS were retrospectively assessed by the Posttraum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The prevalence of emotional abuse and neglect were higher among women (7.5% and 31.1% respectively) than men (4.5% and 24.0% respectively). Previous reports indicated that female alcohol abusers (Bailey, Baker, Mcelduff, & Kavanagh, 2016) and female inmates (Chen & Gueta, 2016) were more likely than males to experience emotional abuse or neglect. A study also found that female high school students who experienced emotional/sexual abuse had a higher prevalence of lifetime opioid use than male students in China (Lei et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of emotional abuse and neglect were higher among women (7.5% and 31.1% respectively) than men (4.5% and 24.0% respectively). Previous reports indicated that female alcohol abusers (Bailey, Baker, Mcelduff, & Kavanagh, 2016) and female inmates (Chen & Gueta, 2016) were more likely than males to experience emotional abuse or neglect. A study also found that female high school students who experienced emotional/sexual abuse had a higher prevalence of lifetime opioid use than male students in China (Lei et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This is because neonatal rats experiencing maternal deprivation showed anomalous behaviors in adulthood which are also observed in schizophrenic patients [ 46 ]. Furthermore, similar mechanisms could occur in development of stress-related disorders, including depression, anxiety disorders and alcoholism [ 47 , 48 ], which could be observed also in “depressive-like” animal model [ 49 ]. Animal studies indicated that early maternal deprivation is associated with increase in the number of degenerating hippocampal neurons and astrocytes and increased corticosterone and implicating the endocannabinoid system as 2-AG levels increased in the hippocampus [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence rates of PTSD and depression in sexually assaulted women are both estimated to be more than 30% (Zinzow et al 2012). Exposure to lifetime sexual violence often results in an elevated likelihood of PTSD and major depressive disorder (Bailey et al 2016). Sexual assault victims most commonly report distress with the physical effects of the assault as well as heightened fear and anxiety when in public places (Fuller 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, sexual assault was found to be an independent risk factor for incident psychiatric disorders after adjustment for potential confounding factors. People who have been sexually assaulted are more likely to report depressive symptoms compared with people who have not been sexually assaulted (Bailey et al 2016). The prevalence rates of PTSD and depression in sexually assaulted women are both estimated to be more than 30% (Zinzow et al 2012).…”
Section: Discussionmentioning
confidence: 99%